1998
DOI: 10.1287/inte.28.3.144
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic HIV-Transmission Model for Evaluating the Costs and Benefits of Vaccine Programs

Abstract: We developed a dynamic model of HIV transmission to evaluate the costs and benefits of HIV-vaccine programs in a population of homosexual men. We examined how changes in high-risk sexual behavior and the growth pattern of the epidemic influence the cost-effectiveness of preventive vaccines and of therapeutic vaccines. We found that the effect of reductions in condom use is more important for therapeutic vaccines than for preventive vaccines. Therapeutic vaccines may increase HIV seroprevalence in the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…18,23,25 To our knowledge, this also represents the first time that differential condom use behavior between men and women has been incorporated into a model of HIV disease transmission. Although Western models of HIV transmission have specified that condom use between 2 partners with differing practices is the greater of the 2 (eg, if one person uses condoms 70% of the time and another person uses condoms 30% of the time, condom use in that particular partnership is 70%), 25 we believe that this does not accurately reflect condom use negotiation in the African setting. We assumed exclusive male negotiation of condom use in our model to reflect the decreased ability of South African women to negotiate condom use in heterosexual partnerships, 60-63 a disadvantage attributable to cultural and economic barriers that is found in many countries throughout sub-Saharan Africa and, in part, explains the shift toward a female-dominated epidemic.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…18,23,25 To our knowledge, this also represents the first time that differential condom use behavior between men and women has been incorporated into a model of HIV disease transmission. Although Western models of HIV transmission have specified that condom use between 2 partners with differing practices is the greater of the 2 (eg, if one person uses condoms 70% of the time and another person uses condoms 30% of the time, condom use in that particular partnership is 70%), 25 we believe that this does not accurately reflect condom use negotiation in the African setting. We assumed exclusive male negotiation of condom use in our model to reflect the decreased ability of South African women to negotiate condom use in heterosexual partnerships, 60-63 a disadvantage attributable to cultural and economic barriers that is found in many countries throughout sub-Saharan Africa and, in part, explains the shift toward a female-dominated epidemic.…”
Section: Discussionmentioning
confidence: 88%
“…[9][10][11][12][13][14] Models have shown that even a partially effective HIV vaccine with minimal efficacy could have an enormous population impact on the HIV epidemic in high-risk groups or areas with a high prevalence of HIV, such as sub-Saharan Africa, [15][16][17][18][19][20][21][22] but that the magnitude of this impact depends on a fine balance between the efficacy of the vaccine, the vaccine coverage level, and the change in risky behavior. 18,20,[23][24][25][26][27] …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations